META ANALISIS : PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SD - Christopher Dean; Ronan Beema Nugraha (STKIP Subang, 2024)
The preparation of a meta-analysis aims to understand the success of the influence of problem-based learning models on improving students' science learning outcomes at the elementary school level. By analyzing various relevant studies using qualitative methods, this research focuses on the advantages of problem-based learning models in improving student learning outcomes by collecting previous research by searching for articles or journals from Google Scholar. The results of the analysis indicate that the use of Problem Based Learning models can have a significant impact on improving students' science learning outcomes at the elementary school level.